The Effect of Work Culture and Personality Toward Teacher’S Organizational Commitment on Public Junior High School - Kei Kecil - Southeast Maluku: Pengaruh Budaya Kerja dan Kepribadian Terhadap Komitmen Organisasi Guru di Smp Negeri Se - Kei Kecil – Kabupaten Maluku Tenggara - Elewarin, Subhan (Procedia of Social Sciences and Humanities, 2022)
The objective of this causal research was to obtain information concerning: (1) the effect of work culture toward organizational commitment; (2) the effect of personality toward organizational commitment; and (3) the effect of work culture toward personality. The research was conducted by using a survey method with path analysis ini testing hypothesis. Ini this research, teachers on Public Junior High School – Kei Kecil-Southeast Maluku has been choosen as a unit analysis and 112 samples of teachers were selected in random. The results of the research are as follows: (1) there is a direct positive effect of work culture toward organizational commitment; (2) there is a direct positive effect of personality toward organizational commitment; and (3) there is a direct positive effect of work culture toward personality.